2017
DOI: 10.1038/s41598-017-12208-7
|View full text |Cite
|
Sign up to set email alerts
|

Loss of MAPK-activated protein kinase 2 enables potent dendritic cell-driven anti-tumour T cell response

Abstract: Maintaining dendritic cells (DC) in a state of dysfunction represents a key mechanism by which tumour cells evade recognition and elimination by the immune system. Limited knowledge about the intracellular mediators of DC dysfunction restricts success of therapies aimed at reactivating a DC-driven anti-tumour immune response. Using a cell type-specific murine knock-out model, we have identified MAPK-activated protein kinase 2 (MK2) as a major guardian of a suppressive DC phenotype in the melanoma tumour microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Our results postulated that MK2 KD tends to stabilize the MKP-1 transcripts, thus, confirming the hypothesis that mRNA stabilization of this negative regulator possibly inhibits the progression of HNSCC. Our findings are in agreement with the latest report showing that systemic MK2 deletion reduced tumor burden by immunomodulatory cancer therapies in mice [35].…”
Section: Discussionsupporting
confidence: 94%
“…Our results postulated that MK2 KD tends to stabilize the MKP-1 transcripts, thus, confirming the hypothesis that mRNA stabilization of this negative regulator possibly inhibits the progression of HNSCC. Our findings are in agreement with the latest report showing that systemic MK2 deletion reduced tumor burden by immunomodulatory cancer therapies in mice [35].…”
Section: Discussionsupporting
confidence: 94%
“…The stimuli tested in the above experiments are harmful for cells and eventually result in cell death. However, p38α and MK2 are known to be activated also in physiological situations that do not necessarily lead to cell death, such as cytokine production in immune cells or during cell differentiation (7,27,28). To analyze the behavior of MK2 in these scenarios, we stimulated bone marrow-derived macrophages (BMDM) with lipopolysaccharide (LPS).…”
Section: Resultsmentioning
confidence: 99%
“…MK2, a key effector kinase of the p38MAPK pathway, regulates multiple critical aspects of the innate immune system cells, including neutrophils ( 50 – 52 ), dendritic cells ( 53 – 55 ) and macrophages ( 56 , 57 ). There is growing evidence that p38/MK2 pathway significantly contributes to inflammation-driven tumorigenesis at multiple levels, since elegant studies from the Nebreda lab have shown that epithelial p38α activity is required for tumor maintenance while myeloid p38α regulates both inflammatory cell recruitment to tumors and chemokine production ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%